1996
DOI: 10.1002/bimj.4710380616
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ratio Using Rank Set Sampling

Abstract: summaryRanked set sampling (RSS) as suggested by MCINTYRE (1952) and developed by TAMHASI and WAKI- MOTO (1968) is used to estimate the ratio. It is proved that by using RSS method the efficiency of the estimator relative to the simple random sampling (SRS) method has increased Computer simulated results are given. An example using real data is presented to illustrate the computations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 10 publications
0
78
0
Order By: Relevance
“…2) DERSS is an extension to ERSS procedure by Samawi (2001). The procedure is just similar to that for DRSS, but taking ERSS instead of RSS in the first and in the second stage.…”
Section: Employ Again the Rss Procedures Inmentioning
confidence: 99%
See 4 more Smart Citations
“…2) DERSS is an extension to ERSS procedure by Samawi (2001). The procedure is just similar to that for DRSS, but taking ERSS instead of RSS in the first and in the second stage.…”
Section: Employ Again the Rss Procedures Inmentioning
confidence: 99%
“…Also, the ratio estimation method is used to obtain increased precision of estimating the population mean or total by taking advantage of the correlation between an auxiliary variable X and the variable of interest Y. In this paper, we assume that the Ratio Estimator Using RSS Samawi and Muttlak (1996) showed that the ratio estimator using RSS when ranking is on the variable X, is …”
Section: Ratio Estimatorsmentioning
confidence: 99%
See 3 more Smart Citations